2003
DOI: 10.1075/aralss.17.09hov
|View full text |Cite
|
Sign up to set email alerts
|

What learners use and how they react

Abstract: This paper outlines the findings of a two-year evaluation of learner use of software tools in a multimedia software package for teaching Indonesian listening comprehension and culture. This software package was introduced into the Introductory language program to help address the need of total beginners for exposure to native speakers using daily language in ordinary ways, on common, everyday topics. The package is designed to introduce, develop, and reinforce appropriate learning strategies at the same time. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 0 publications
0
13
0
Order By: Relevance
“…It is not surprising that learners become dissatisfied and lose their interest and motivation necessary to continue the tasks when the technology frequently breaks down or programs crash (Herrington & Oliver, 1997;Hoven, 2003). Several researchers have found that learners' perceived value of their learning experience using technology partially depends on the transparency and robustness of the technology (Downes, 2000;Hoven, 2003).…”
Section: Resultsmentioning
confidence: 99%
“…It is not surprising that learners become dissatisfied and lose their interest and motivation necessary to continue the tasks when the technology frequently breaks down or programs crash (Herrington & Oliver, 1997;Hoven, 2003). Several researchers have found that learners' perceived value of their learning experience using technology partially depends on the transparency and robustness of the technology (Downes, 2000;Hoven, 2003).…”
Section: Resultsmentioning
confidence: 99%
“…Clearly, varied results on the relationship between help option use and performance (positive relationship in Jones, 2003;Jones & Plass, 2002;Grgurović & Hegelheimer, 2007; no relationship in Liou, 1997Liou, , 2000Pujolà, 2002; negative relationship in Hegelheimer & Tower, 2004) point to the need for further research in help option usage in listening environments. Hoven (2003) observed variations between students of differing levels of proficiency. Hoven found that students' attitudes towards the language program changed as they became more familiar working with it.…”
Section: Frequency Of Use Of Help Options and Performance In Listeninmentioning
confidence: 94%
“…We group these factors into two categories: factors related to research design and factors related to materials design (see Table 9). Limited number of participants Hsu (1994), Liou (1997), Chun (2001), Al-Seghayer (2001), Chun & Payne (2004), Hoven (2003), Pujolà (2002), Ggurović & Hegelheimer (2007), Cárdenas-Claros (2005) Limited sources of data interpretation Hegelheimer & Tower (2004), Grace (2000) Time constraints Liou (1997Liou ( , 2000, Kaur & Hegelheimer (2005), Ariew & Ercetin (2004), Grgurović & Hegelheimer (2007) Materials design factors…”
Section: Common Research Methods and Problemsmentioning
confidence: 99%
“…When learning online students of different abilities will be expected to behave differently and perform differently. On the one hand, high proficiency learners have been found to feel more comfortable exploring the various options available with the technology (Hoven, 2003); on the other hand, weaker learners are allowed to proceed gradually and steadily.…”
Section: Teacher-student Interactionmentioning
confidence: 99%